Cholinesterase Inhibitors and Pisa Syndrome: A Pharmacovigilance Study. Issue 3 (11th October 2013) - Zannas, Anthony S.; Okuno, Yasushi; Doraiswamy, P. Murali
<x xml:space="preserve">Abstract</x> Study Objectives Case reports suggest a relationship between cholinesterase inhibitors (ChEIs) and Pisa syndrome (PS), also known as pleurothotonus, a form of dystonia, but this relationship has not been systematically examined. Our objective was to estimate the adjusted reporting ratios of PS with donepezil, rivastigmine, and galantamine in the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. Design Retrospective analysis of adverse event reports in the FAERS database. Patients Patients with drug‐related adverse events in the FAERS database. Measurements and Main Results The Gamma Poisson Shrinker algorithm was used to estimate the empirical Bayes geometric mean (EBGM) along with the lower and upper 90% confidence interval (CI) limits (EB05 and EB95, respectively), as measures of the adjusted reporting ratio of PS in patients taking ChEIs. EB05 > 2.0 was used as the cutoff for significance for the signals. The EBGM (EB05) was 37.9 (30) for all ChEIs, 25.6 (17.6) for donepezil, 76.4 (50.3) for galantamine, and 33.7 (21.2) for rivastigmine. All adverse event signals were strongly significant based on the a priori set EB05 cutoff. The female:male ratio in the reported cases was 2:1. No significant signals were found between ChEIs and other dystonias. About half of the ChEI users were also taking concomitant antipsychotics. Conclusion Although FAERS data cannot establish causality due to reporting biases, our findings support a potential dopaminergic‐cholinergic imbalance as an underlying mechanism for PS and may help increase clinician awareness, early identification, and treatment of ChEI‐related dystonias.